MEDIA VIDEO PEMBELAJARAN ADMINISTRASI DAN SUPERVISI PENDIDIKAN UNTUK OPTIMALISASI PERKULIAHAN DARING MELALUI METODE PEMBELAJARAN BLENDED LEARNING-FLIPPED CLASSROOM - Sembiring, Desy A. K. (NOKEN : Jurnal Pengelolaan Pendidikan, 2021)
The Covid-19 pandemic requires lecturers and students to carry out online learning activities in accordance with Surat Edaran Nomor 15 Tahun 2020 concerning Pedoman Penyelenggaraan Belajar dari Rumah dalam Masa Darurat Penyebaran Covid-19. Changes in  using  technology  to  modify  media  and  learning  methods  need  to  be  implemented, including in Administrasi dan Supervisi Pendidikan subject at the Program Studi Manajemen Pendidikan, Cenderawasih University, in implementing learning video and Blended Learning- Flipped Classroom (BLFC) learning method. The purpose was to implement instructional video and Blended Learning-Flipped Classroom learning method for Administrasi dan Supervisi Pendidikan students. The method used was the implementation of making learning video and Blended Learning-Flipped Classroom learning method, giving pretest and posttest and distributing questionnaires as data collection results from the implementation. The results showed that there was a positive response from students through learning beforehand using asynchronous learning videos and conducting synchronous discussions which were collaborated using the cognitive realm of Bloom's taxonomy in order to realize a directed and structured learning process. This response was supported by the results of the pretest and posttest showing an increase in understanding by 23 percent and also 90 percent of students suggesting to continue using learning videos in online learning.Keywords: Covid-19; online learning; Learning Video; BLFC